Community Engagement through Medical Missions - Charles P. Seeley; Yudy Canelas; Peggy Hook; Valerie Schubert (Journal of Scholarly Engagement)
The idea for this article was planted in a conversation between the lead author and one of the co-authors in mid-2019, well before the outbreak of the coronavirus pandemic around the world. We began work on this article late in 2019; in hindsight, life then was much simpler given that COVID-19 has already changed the world in many ways. As a result, this article examines community engagement through medical missions in the world as it existed prior to the onslaught of COVID-19. The setting for this look into community engagement through medical missions in the country of Honduras.